Marine structural design - Bai, Yong (Elsevier, 2003)
This new reference describes the applications of modern structural engineering to marine structures. It will provide an invaluable resource to practicing marine and offshore engineers working in oil and gas as well as those studying marine structural design. The coverage of fatigue and fracture criteria forms a basis for limit-state design and re-assessment of existing structures and assists with determining material and inspection requirements. Describing applications of risk assessment to marine and offshore industries, this is a practical and useful book to help engineers conduct structural design. *Presents modern structural design principles helping the engineer understand how to conduct structural design by analysis *Offers practical and usable theory for industrial applications of structural reliability theory